Re-evaluating the practice of hibah trust in Malaysia - Noordin, Nazrul Hazizi; Ismail, Muhammad Issyam; Abd Rahman, Muhammad Abd Hadi; Haron, Siti Nurah; Abdullah, Adam (Emerald Group Publishing Ltd, 2016)
Purpose – This paper aims to re-evaluate and thus recommending possible ways in improving the current practice of hibah trust in Malaysia. Design/methodology/approach – This study conducts a thorough and critical review on relevant literature on Islamic wealth management and estate distribution. Besides, the current practice and application of hibah trust by the Malaysian trustee companies such as Amanah Raya Berhad and As-Salihin Trustee Berhad is analyzed based on information gathered from their publications and direct consultation. Findings – Based on the comparison made between hibah trust and its conventional counterpart, living trust, this study found that that the hibah trust product mirrors the conventional living trust, which provides a high degree of freedom to the benefactor to decide on the distribution of his wealth without taking into consideration the interest of the eligible heirs under farai’d. Nevertheless, it is undeniable that the practice of hibah trust would be able to expedite the lengthy and complex procedures of inheritance, reduce administrative costs, avoid legal impediments and inheritance tax. Practical Implications – This paper proposes a comprehensive framework for an improved asset distribution under hibah trust within the Malaysian Islamic wealth management industry by highlighting the significance of fara’id and wasiyyah rules. This proposed framework of hibah trust would become a useful reference for the policy-makers in designing a dedicated regulation or legal provisions in the established laws that will govern the practice of hibah trust in Malaysia. Originality/value – The novelty of this paper lies in highlighting the importance of adhering to the law of Islamic inheritance rules as ordained by Allah s.w.t in structuring contemporary Islamic estate planning instruments such as hibah trust, which is not evident in the current practice.